Urban dimension and perception at the Classic Maya city of Palenque - Campiani, Arianna (Restauro Compás y Canto S.A., 2021)
In this article I address two interrelated topics: space construction and the perception of the built environment at Palenque, Chiapas, during the Late Classic Period. Starting from the study of Palenque’s urban morphology and by using Geographic Information System’s tools, I aim at underlying intentionality in specific buildings’ position and to explore how people’s urbanity, that is their condition in the city and the experience of otherness, would have transformed their perception of the environment. To this end, I will consider some characteristics of the environment such as labor investment, infrastructure and resource access, land subdivision in architectural groups and their distribution. I argue that these elements, if considered in relation with circulation and visibility, suggest specific planning strategies and point to social status difference within city sectors and their inhabitants.